Ultrafast dynamics of temporary anions probed through the prism of photodetachment. Issue 4 (1st October 2016) - Anstöter, Cate S.; Bull, James N.; Verlet, Jan R.R.
Abstract : The recently developed method of frequency-, angle-, and time-resolved photoelectron imaging (FAT-PI) applied to the study of the dynamics of resonances of open-shell anions is reviewed. The basic principles of the method and its experimental realisation are outlined. The dynamics of a number of radical quinone anions is then considered. Firstly, we show for para-benzoquinone how frequency- and angle-resolved photoelectron imaging provides finger-prints of the dynamics of resonances and then how time-resolved photoelectron imaging yields deep mechanistic insight into the relaxation dynamics of the resonances. The effect of chemical substitutions of the para-quinone electrophore on the dynamics of resonances is discussed. Increasing the conjugation leads to a greatly enhanced ability for resonances to decay to the ground electronic state of the radical anion. Using time-resolved photoelectron spectroscopy, it is shown that the dynamics are facilitated by a bound valence state of the anion. The addition of electron donating methoxy groups leads to a reduced ability to access the ground state compared to para-benzoquinone. Both time-resolved dynamics and calculations provide a rationale for these observations. We consider the benefits and limitations of FAT-PI and its complementarity to 2D electron spectroscopy.